In vivo and in situ measurement and modelling of intra‐body effective complex permittivity. Issue 6 (30th November 2015) - Nadimi, Esmaeil S.; Blanes‐Vidal, Victoria; Harslund, Jakob L.F.; Ramezani, Mohammad H.; Kjeldsen, Jens; Johansen, Per Michael; Thiel, David; Tarokh, Vahid
Abstract : Radio frequency tracking of medical micro‐robots in minimally invasive medicine is usually investigated upon the assumption that the human body is a homogeneous propagation medium. In this Letter, the authors conducted various trial programs to measure and model the effective complex permittivity ε in terms of refraction ε′, absorption ε″ and their variations in gastrointestinal (GI) tract organs (i.e. oesophagus, stomach, small intestine and large intestine) and the porcine abdominal wall under in vivo and in situ conditions. They further investigated the effects of irregular and unsynchronised contractions and simulated peristaltic movements of the GI tract organs inside the abdominal cavity and in the presence of the abdominal wall on the measurements and variations of ε′ and ε′′. They advanced the previous models of effective complex permittivity of a multilayer inhomogeneous medium, by estimating an analytical model that accounts for reflections between the layers and calculates the attenuation that the wave encounters as it traverses the GI tract and the abdominal wall. They observed that deviation from the specified nominal layer thicknesses due to non‐geometric boundaries of GI tract morphometric variables has an impact on the performance of the authors' model. Therefore, they derived statistical‐based models for ε′ and ε′′ using their experimental measurements.